Weed Management in Home Lawns - J. Bryan Unruh; Barry J. Brecke; Laurie E. Trenholm (EDIS)
Revised! ENH-884, a 9-page fact sheet by J. Bryan Unruh, Barry Brecke, and Laurie E. Trenholm, provides homeowners with information to carry out a carefully planned and coordinated weed control program for their lawns. Describes types of weeds, proper lawn management, weed biology and control, weed control prior to turf establishment and in established turf, and pesticide application procedures. Published by the UF Department of Environmental Horticulture, April 2008.